Kinematic variations across Eastern Cordillera at 24°S (Central Andes): tectonic and magmatic implications - Acocella, V. (2007)
The Eastern Cordillera (Central Andes, ∼ 24°S) consists of a basement-involved thrust system, resulting from Miocene-Quaternary eastward migrating compression, separating the Puna plateau from the Santa Barbara System foreland. The inferred Tertiary strains arising from shortening in the Eastern Cordillera and Santa Barbara System are similar, higher than in the Puna. Slip data collected on the major ∼ N-S trending faults of Eastern Cordillera show a westward progression from dip-slip (contraction) to dextral and sinistral motions. This, consistently with established tectonic models, may result from partitioning due to the oblique Mio-Quaternary underthrusting of the Brazilian Shield north of 24°S. This strain partitioning has three main implications. (1) As the dextral and sinistral shear in the Eastern Cordillera are ∼ 62% and 29% of the compressive strain respectively, the Eastern Cordillera results more strained than Santa Barbara System foreland, contrary to previous estimates. (2) The partitioning in the Eastern Cordillera may find its counterpart in that to the west of the Central Andes, giving a possible structural symmetry to the Central Andes. (3) The easternmost N-S strike-slip structures in the Eastern Cordillera coincide with the easternmost Mio-Pliocene magmatic centres in the Central Andes, at ∼ 24°S. Provided that, further to the east, the crust is partially molten, the absence of magmatic centres may be explained by the presence of pure compressive structures in this portion of the Eastern Cordillera.